On (α + uβ)-constacyclic codes of length 4ps over ð ½pm + uð ½pm∗ - Hai Q. Dinh (2018)
© 2019 World Scientific Publishing Company For any odd prime (Formula presented.) such that (Formula presented.) (mod 4), the structures of all (Formula presented.)-constacyclic codes of length (Formula presented.) over the finite commutative chain ring (Formula presented.) (Formula presented.) are established in term of their generator polynomials. When the unit (Formula presented.) is a square, each (Formula presented.)-constacyclic code of length (Formula presented.) is expressed as a direct sum of two constacyclic codes of length (Formula presented.). In the main case that the unit (Formula presented.) is not a square, it is shown that the ambient ring (Formula presented.) is a principal ideal ring. From that, the structure, number of codewords, duals of all such (Formula presented.)-constacyclic codes are obtained. As an application, we identify all self-orthogonal, dual-containing, and the unique self-dual (Formula presented.)-constacyclic codes of length (Formula presented.) over (Formula presented.).